A description of a new species of Cephalodasys (Macrodasyida: Gastrotricha) from Florida, USA using an integrative morphological approach - Araújo, Thiago Quintão (Zootaxa, 2024)
A new gastrotrich species of the genus Cephalodasys (Macrodasyida: Cephalodasyidae) is described from Capron Shoal, Florida, USA. The new species is up to 630 μm long. There are six TbA that arises directly from a fleshy hand-like base. Up to 26 TbVL per side. 11 pairs of TbV running from U28 to U65. 12 pairs of TbP arranged symmetrically along the posterior margin from U90 to U100. Animals are simultaneous hermaphrodites with a rounded frontal organ and a putative caudal organ. On the other hand, the new species is unique and differs from its congeners by the arrangement of anterior, posterior and ventrolateral adhesive tubes and by exclusive series of TbV, first time reported in Cephalodasys. A complete set of longitudinal, circular and helicoidal muscles are described for the first time for a Cephalodasys species using Confocal Laser Scanning Microscopy (CLSM). The muscular analysis added important novelties to the knowledge of muscular architecture of Macrodasyida group and to the phylum.